2022
DOI: 10.1016/j.jadr.2022.100321
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety and social health among health care workers and health volunteers exposed to coronavirus disease in Iran (2020): A structural equation modeling

Abstract: Objective The purpose of this study was to examine the structural relationships between health anxiety and social health among Health Care Workers exposed to covid-19 in Iran. Method The research was an online-survey and cross-sectional study. The sample consisted of 735 Health Care Workers and health volunteers in Iran from 13 April to 4 May 2020. Three standardized pre-tested questionnaires were used to collect data including social health, health anxiety and corona-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Stress and anxiety can weaken the immune system and make a person vulnerable to disease [ 24 ]. Health anxiety along with high workload can lead to burnout and psychological distress in HCWs [ 25 , 26 ]. Healthcare workers are at the forefront of the fight against COVID-19 and play a key role in controlling the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Stress and anxiety can weaken the immune system and make a person vulnerable to disease [ 24 ]. Health anxiety along with high workload can lead to burnout and psychological distress in HCWs [ 25 , 26 ]. Healthcare workers are at the forefront of the fight against COVID-19 and play a key role in controlling the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of education is to increase patient and family awareness, reduce anxiety, increase patient independence and capability, adapt to disease conditions and complications, know how to use social and economic resources, increase patient satisfaction, and reduce patient readmission. Education varies based on the services provided in hospitals and target groups (elderly, child abuse, addicts, patients with mental disorders) and the social worker can use individual, group education methods, publication of brochures, and educational booklets (Craig et al, 2020; Gibbons and Plath, 2012; Javadi, 2022; Sabzi Khoshnami et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…40 Another study in Iran found that the proportion of anxiety was high in healthcare providers, reaching 51%. 41 Another study found that the an xiety of healthcare providers during the COVID-19 pandemic reached 41.4%. 42 A study in the UK stated that the anxiety of healthcare providers increased from a score of two (before the pandemic) to a score of seven (during the pandemic).…”
Section: Discussionmentioning
confidence: 99%
“…40 A study in Iran on anxiety reported that marital status, age, employment status, and type of healthcare provider were associated with anxiety. 41 Another study found that job insecurity, infection of family members, and an increase in severe illnesses and deaths were associated with anxiety among healthcare providers. 42 A study in the UK found that patient and family exposure factors, SARS-CoV-2 exposure, insufficient PPE and testing, too much information, job uncertainty, inaccurate information, financial instability, and lack of information were the main reasons for anxiety among healthcare providers.…”
Section: Discussionmentioning
confidence: 99%